Strategies to increase photodynamic theraph efficacy on conventional and complex in vitro cancer models - Ruhi, Mustafa Kemal. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2019., 2019)
Cancer is one of the leading causes of death worldwide. Due to the side-eﬀects and ineﬃcacy of the conventional cancer treatment methods, alternative modalities are researched. Oneofthealternatives, PhotodynamicTherapy(PDT),isaphotochemical approach, which is based on the activation of a photosensitive chemical (photosensitizer) by a speciﬁc light source for creating reactive oxygen species that are toxic to cancer cells. A number of in vitro and in vivo studies, as well as clinical trials, are conducted every year for increasing the eﬃcacy of PDT. Combining diﬀerent photosensitizers or developing new nanoconjugations for better targeting are some of the strategies. Apart from monolayer cell cultures and in vivo animal models, another important tool for testing new cancer treatment strategies is an advanced in vitro model that mimics certain physiological factors in tumor microenvironment. These factors include cell-to-cell interactions, hypoxic environments and some mechanical stresses that may aﬀect tumor progression. This PhD study proposes diﬀerent strategies to increase photodynamic therapy eﬃcacy and tests these new protocols on conventional and complex in vitro models. The outcomes of the studies not only show the success of the proposed strategies, but also reveals the importance of in vitro models for cancer research.|Keywords : Photodynamic Therapy, Cancer, 3D Cell Culturing, Targeting Strategies, In Vitro Models.
Keywords: Photochemotherapy.; Cancer.